Factors influencing green product purchase behavior among University Putra Malaysia students - Md Jusoh, Zuroni; Mahalingam, Thaneswary (AMH International, 2023)
The issue of the environment such as increasing sea levels, air pollution, water pollution, and climate change, are affecting people all over. Since early times, human beings have been experiencing environmental degradation due to the development activities due to the rise of civilizations. A green product is designed to have as little environmental impact as possible over its entire life cycle, including after it is no longer being used. This study examines the factors influencing green product purchase behaviour among University Putra Malaysia (UPM) students. A total of 260 respondents were selected from the University of Putra Malaysia by using simple random sampling. The data was collected by using the administered questionnaire. The results of multiple linear regressions showed that the adjusted R2 is 0.438, indicating that the variance of the dependent variable was explained by the knowledge, attitude, social appeal and emotional value. The result also showed only three variables were influencing; emotional value (ß =.333, p ? 0.01) was the most influential factor, followed by knowledge (ß =.303, p ? 0.01) and attitude (ß =.160, p ? 0.01) among UPM students towards the green product purchase behaviour. This study concluded that emotional value, knowledge, and attitude were among the factors influencing green product purchase behaviour. Future research is recommended to conduct this study on other University students in Malaysia with larger samples and also can focus on the other factors which influence the students on green product purchase behaviour.